Wait Time : A Memoir of Cancer - Sherman, Kenneth, 1950- (Book collections on Project MUSE., 2016)
"When poet and essayist Kenneth Sherman was diagnosed with cancer, he began keeping a notebook of observations that blossomed into this powerful memoir. With incisive and evocative language, Sherman presents a clear-eyed view of what the cancer patient feels and thinks. His narrative voice is personal but not confessional, practical but not cold, thoughtful and searching but not self-pitying or self-absorbed. "--Publisher's website.